Caracterização nutricional e atividade biológica de folhas orgânicas de cenoura (daucus carota l.) - Leite, Maria Clerya Alvino (2010)
Non-conventional leafy vegetables can be used as food in adequate quantities as an alternative source of nutrients. However, before its consumption, should take into account their nutritional composition, which depends on its bioavailability and the absence of cytotoxicity and anti-nutritional factors. In this study, leaves of carrot were analyzed to determine the proximate composition, antinutritional factors and haemolytic activity, antibacterial and antifungal. Chemical composition and content of antinutritional factors (lectins, tannins and saponins) were determined in fresh leaves, bleached, boiled and lyophilized. For extraction of proteins, we used six solutions under stirring for 3 hours at 25°C, and the crude extract. Hemagglutination assay was determined by double serial dilution of the extract in test tubes containing saline and erythrocytes at 3% of human blood A and B, and rabbit. We investigated the specificity of the lectin by sugars using inhibition with many simple carbohydrates. Soluble proteins was performed by Bradford method. The inactivation of the lectin was tested with the crude extract with a pH variation (2.08 to 13.08) and temperature (40 to 100º C). Protein extract was precipitated with ammonium sulfate at 80% saturation, obtaining the active fraction (0-80). This was subjected to affinity chromatography (stromapolyacrylamide) and used to check the resistance of the lectin against chelating agents, denaturants, reducing agents, oxidants and proteolytic enzymes (trypsin, papain and bromelain). After treatment of the lectin with these agents, there was testing hemagglutination activity (HA). Tannins were determined using tannic acid as standard and the hemolytic activity of saponin for the search. Tests were carried out for antibacterial, antifungal and haemolytic with the protein fraction. The HA was best seen when using 0.15 M NaCl. Among the erythrocytes tested lectin preferentially agglutinated rabbit treated and not treated with proteolytic enzymes (154.26 HU/mgP), with specificity for the carbohydrate lactose, galactose and arabinose. It was found that the lectin is inactivated at temperatures from 100ºC and at acid pH 2.08. Lectin sample was resistant to proteolytic enzymes, reducing agent, oxidizing and denaturing for 30 minutes. However, the total loss of HA occurred with the administration of chelating agent on the day and overnight after denaturing. Ions in the presence of isolated HA was maintained. Chromatography showed a peak that had HA and protein profile of fractions and the active peaks and no assets were subjected to electrophoresis on polyacrylamide gel in the presence of sodium dodecyl sulfate (SDS), indicating a partial purification. Total tannin contents ranged from 0,16% to 0,60% cooked leaf to fresh leaf. Research saponin was negative in the sample. The protein fraction showed no inhibitory effect on the growth of dermatophyte fungi, however, showed activity against Staphylococcus aureus and Escherichia coli with a minimum inhibitory concentration of 1,9 μg/mL of protein. Samples tested did not cause hemolytic effect against human erythrocytes A and B. We conclude from this study that the carrot leaves have nutritional properties that enable it to use. It also has anti-nutritional factors that are inactivated by heat.